Seasonal life cycle of the lone star tick (Amblyomma americanum) and the influence of prescribed burning on tick abundance and presence of microorganisms - Salazar Aguirre, Andrea Mercedes (My University, 2025)
The lone star tick (Amblyomma americanum) is the most common and widely distributed tick species in the Central and Eastern United States and dominates tick communities in the Kansas Flint Hills. All life stages of A. americanum feed on humans as well as a variety of vertebrate hosts, serving as vectors for several pathogens, such as Ehrlichia chaffeensis, Ehrlichia ewingii, Francisella tularensis, and Heartland virus. In addition to pathogen transmission, infestations of this tick can cause irritation, blood loss, and reduced productivity in livestock. This dissertation examined the ecology of A. americanum in the Kansas Flint Hills and evaluated prescribed burning as a long-term, sustainable method to manage tick populations and reduce tick-borne pathogen burdens. The research was conducted at the Kansas State University Beef Stocker Unit, a tallgrass prairie site where prescribed burning was applied in different seasons (spring, summer, and fall). Understanding how prescribed fire affects tick abundance, seasonal activity, and pathogen presence is integral to developing integrated management practices that protect human and animal health. In Chapter 2, the seasonal life cycle of A. americanum populations under field conditions in Kansas was studied. Field collections suggest that the life cycle takes two years to complete, which was similar to reports from other regions in the Central United States. In year one, adults lay eggs in early summer, and larvae emerge from late July through October. Fed larvae or newly molted nymphs overwinter, with nymphs reappearing as early as March in year two. Nymph ticks remain active through summer, molting into adults by late summer or fall. In Chapter 3, I evaluated the effects of long-term prescribed burning on A. americanum populations. The results showed a significant reduction in tick abundance in burned pastures compared to the unburned control. Burns performed in the spring were seen to be the most effective. Consecutive applications of prescribed burning over several years kept a low tick population, which indicates a lasting suppressive effect of the fire. In Chapter 4, the impact of prescribed burning on the presence of microorganisms in field-collected A. americanum was investigated. Overall, 36.7% of ticks were positive for Rickettsia spp., 8.3% for E. chaffeensis, and 5.3% for E. ewingii, while R. rickettsii and F. tularensis were not detected. Although prescribed burning significantly reduced tick abundance, it did not affect the presence of tested microorganisms across treatments. Co-occurrence analysis showed that E. chaffeensis and E. ewingii were detected together more often than expected by chance, suggesting possible interactions within the tick or during feeding; the two species were acquired from the same host. In general, this research contributes to a better understanding of A. americanum ecology, its response to prescribed fire, and pathogen dynamics in the Flint Hills region.
Keywords: Tick; Amblyomma americanum; Prescribed burning; Tick abundance; Microorganism presence; Lone star tick